(untitled) (Cadernos de Sociomuseologia, 2015)
This paper discusses some aspects of the Declaration MINOM Rio 2013. The text shows the importance of this Declaration in the context of the early twenty-first century. The practical proposal of the document allows its use in other areas of knowledge and other segments of society. Therefore, the article presents two virtues of the Declaration: the questioning of established hierarchies and the presence of a hermeneutics of transdisciplinarity. Finally, the article concludes with the questions about the survival of these new movements of the community. Therefore proposes the methodology of Negócios Sócio-Sustentáveis WTS. Keywords: Declaration MINOM Rio 2013, Hierarchies, Transdisciplinarity and Negócios Sócio-Sustentáveis WTS.